Pre-Service Teachers' Attitudes Towards Studying Chemistry - Mai, Mohammed Yousef (European Journal of Social Science Education and Research, 2016)
This research aims at investigating the pre-service teachers' attitudes towards chemistry. A researcher used "Chemistry Attitudes and Experiences Questionnaire" (CAEQ) to measure students' experiences and attitude towards chemistry, it has good indices for validity and reliability. This questionnaire has three subcategories, (1) attitudes towards lecturer classes in chemistry, (2) attitudes towards tutorial classes in chemistry and (3) attitudes towards laboratory classes in chemistry. The participants are 70 students (85.7% female and 14.3% male) from the first year students in faculty of science and mathematics (FSM) - UPSI. The findings showed that, the students have moderate attitudes towards lecture class in chemistry, tutorials classes in chemistry and laboratory classes in chemistry. Although there is no significant differences found related to the students' gender or race (except for attitudes and tutoring) but there is an interaction between gender and race concerning the pre-service teachers ' attitude toward chemistry.
Keywords: Pre-service teachers, science education,Chemistry, university, attitudes, laboratory, tutorial.